The Role of Antiplatelet and Antithrombotic Agents in Enhancing the Success of Interventional Cardiological Procedures - Khan, Naeem; Khan, Farhat Ullah; Khan, Muhammad Idrees; Parvez, Muzdalfa; Musa, Muhammad (Indus Journal of Bioscience Research, 2025)
Objective: To investigate the role of antiplatelet and antithrombotic agents in enhancing the success of interventional cardiological procedures, focusing on their impact in reducing thrombotic complications and managing bleeding risks. Methodology: A retrospective study was conducted from January 2023 to December 2023 at Hayatabad Medical Complex, Peshawar. A total of 200 patients were included, with 100 patients in the DAPT group and 100 patients in the single-agent therapy group. Data were collected from patient records, assessing the intervention success, bleeding complications, thrombotic events, and cardiovascular outcomes. Statistical analysis included chi-square tests, independent t-tests, and Kaplan-Meier survival analysis with a significance level of p < 0.05. Results: The DAPT group demonstrated a significantly higher intervention success rate (90%) compared to the single-agent therapy group (80%) (p = 0.032). Bleeding complications were lower in the DAPT group (10%) versus the single-agent therapy group (20%) (p = 0.045). Thrombotic events occurred more frequently in the single-agent therapy group (15%) than the DAPT group (5%) (p = 0.012). No significant differences in cardiovascular events (MI and stroke) were observed between the groups (p = 0.078 and p = 0.180, respectively). Conclusion: DAPT is more effective in preventing thrombotic events and ensuring the success of interventional cardiological procedures, although it carries a higher bleeding risk. These findings support the use of DAPT in clinical practice, with careful management of bleeding risks.